Sheet for power devices and power device member
By using a combined sheet of polyester urea and thermal conductivity filler in a high-power module, the problem of difficulty in achieving low temperature adhesion, electrical insulation and high thermal conductivity in the prior art is solved, and excellent adhesion and thermal conductivity in high-temperature environments are achieved.
Patent Information
- Application Number
- JP2023172286
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-03
- Publication Date
- 2025-04-15
AI Technical Summary
The prior art is difficult to provide a adhesive sheet with both low temperature adhesion and electrical insulation and thermal conductivity for thermal dissipation and electrical reliability requirements of high-power modules.
The flakes formed by combining a standard polyester urea with a volume ratio of 15-60% and a standard thermal conductivity filler (such as oxides, silicates, etc.) with a volume ratio of 40-85% to a volume ratio of 15-60% to a standard thermal conductivity, with high thermal conductivity (5W/(m·K) or higher) and thin thickness (200μm or thinner).
It achieves excellent adhesion and thermal conductivity in high-power modules while maintaining electrical insulation for high temperature environments.
Smart Images

Figure 2025062919000001 
Figure 2025062919000002 
Figure 2025062919000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a power device sheet and a power device member. [Background technology]
[0002] In recent years, semiconductor integrated circuits have been used in various electronic devices. Among them, power modules equipped with power elements such as high-power diodes, transistors, and ICs are used in devices that require large electric power. Power modules are required to have sufficient heat dissipation properties to dissipate heat generated by the power elements, and high electrical insulation properties (electrical reliability) at high temperatures. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2015-108139 A Summary of the Invention [Problem to be solved by the invention]
[0004] Various sheet configurations including heat-resistant resins and thermally conductive fillers have been proposed as adhesive sheets for joining a power module and a heat sink and conducting heat generated in the power module to the heat sink. However, with the increasing output of power modules in recent years, the physical properties required of the sheets tend to become even higher. Specifically, from the viewpoint of processability during bonding, there is a demand for adhesive sheets that are excellent in low-temperature adhesion, and also have electrical insulation and thermal conductivity.
[0005] In view of the above circumstances, the present disclosure provides a power device sheet and power device component that are excellent in adhesiveness and thermal conductivity, as a sheet of a specified thickness comprising a polyimide having excellent flexibility and adhesiveness and a specified thermally conductive filler blended in a specified ratio. [Means for solving the problem]
[0006] The present disclosure includes the following aspects. <1> Polyimide and and at least one filler selected from the group consisting of oxides, nitrides, simple metals, alloys, and carbon, The content of polyimide is 15 to 60 volume % based on the total amount of the power device sheet, The content of the filler is 40 to 85% by volume with respect to the total amount of the power device sheet, The polyimide includes polyimide A which is a reaction product of an aromatic tetracarboxylic anhydride and a diamine having an ether bond or a siloxane bond, or polyimide B which is a reaction product of an aromatic tetracarboxylic anhydride and a polyamine including an aliphatic diamine having 4 to 40 carbon atoms; A sheet for power devices having a thermal conductivity of 5 W / (m K) or more and a thickness of 200 μm or less. <2> Polyimide A is a polyimide which is a reaction product of an aromatic tetracarboxylic acid anhydride with at least one diamine selected from the group consisting of 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-diaminodiphenyl ether, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, poly(propylene glycol)diamine, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane; <1> The power device sheet according to claim 1, <3> Polyimide B is a thermoplastic polyimide which is a reaction product of an aromatic tetracarboxylic acid anhydride, an aliphatic diamine having 4 to 40 carbon atoms and not containing a ring structure, and an aliphatic diamine having 6 to 40 carbon atoms and containing a ring structure. <1> The power device sheet according to claim 1, <4> Polyimide B is a thermoplastic polyimide which is a reaction product of an aromatic tetracarboxylic anhydride, an aliphatic diamine having 4 to 40 carbon atoms, and an aliphatic triamine having 6 to 40 carbon atoms. <1> The power device sheet according to claim 1, <5> The filler is at least one selected from the group consisting of metal oxides, boron nitride, and magnesium metasilicate. <1> ~ <4> 10. The sheet for use in a power device according to claim 9, wherein the first and second electrodes are arranged parallel to the first and second electrodes. <6> Silicon carbide-based power device sheet. <1> ~ <5> 10. The sheet for use in a power device according to claim 9, wherein the first and second electrodes are arranged parallel to the first and second electrodes. <7> A power device member in which a polyimide sheet and a metal sheet are laminated, The polyimide sheet is Polyimide and At least one filler selected from the group consisting of oxides, nitrides, metal elements, alloys, and carbon; The content of polyimide is 15 to 60 volume % based on the total volume of the polyimide sheet, The filler content is 40 to 85% by volume based on the total volume of the polyimide sheet. The polyimide includes polyimide A which is a reaction product of an aromatic tetracarboxylic anhydride and a diamine having an ether bond or a siloxane bond, or polyimide B which is a reaction product of an aromatic tetracarboxylic anhydride and a polyamine including an aliphatic diamine having 4 to 40 carbon atoms; A power device component that is a sheet with a thermal conductivity of 5 W / (m K) or more and a thickness of 200 μm or less. <8> The power device member is a silicon carbide-based power device member. <7> The power device member according to claim 1. Effect of the Invention
[0007] According to one embodiment of the present invention, a power device sheet and a power device member having excellent adhesiveness and thermal conductivity are provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] In the present disclosure, a numerical range indicated using "~" includes the numerical values before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in the present disclosure. The limit values may be replaced by values shown in the examples.
[0009] [Sheets for power devices] The power device sheet of the present disclosure comprises a polyimide and at least one filler selected from the group consisting of an oxide, a nitride, an elemental metal, an alloy, and carbon, the polyimide content being 15 to 60 volume % relative to the total amount of the power device sheet, and the filler content being 40 to 85 volume % relative to the total amount of the power device sheet, the polyimide comprising polyimide A which is a reaction product of an aromatic tetracarboxylic anhydride and a diamine having an ether bond or a siloxane bond, or polyimide B which is a reaction product of an aromatic tetracarboxylic anhydride and a polyamine including an aliphatic diamine having 4 to 40 carbon atoms, and the power device sheet has a thermal conductivity of 5 W / (m·K) or more and a thickness of 200 μm or less.
[0010] <Polyimide> The sheet for a power device according to the present disclosure contains polyimide. The polyimide includes polyimide A which is a reaction product of an aromatic tetracarboxylic anhydride and a diamine having an ether bond or a siloxane bond, and polyimide B which is a reaction product of an aromatic tetracarboxylic anhydride and a polyamine including an aliphatic diamine having 4 to 40 carbon atoms.
[0011] (Polyimide A) Polyimide A is a reaction product of an aromatic tetracarboxylic acid anhydride and a diamine having an ether bond or a siloxane bond.
[0012] Examples of aromatic tetracarboxylic acid anhydrides include those described in JP-A-2013-199645, paragraph
[0019] , JP-A-2017-119361, paragraph
[0011] , JP-A-2017-121807, paragraph
[0023] , and JP-A-2012-145676, paragraph
[0055] .
[0013] The aromatic tetracarboxylic acid anhydride may be used alone or in combination of two or more kinds.
[0014] From the viewpoints of adhesiveness and thermal conductivity, the aromatic tetracarboxylic acid anhydride is preferably a compound represented by the following formula (1).
[0015] [ka]
[0016] In formula (1), X is a single bond, -SO2-, -C(O)-, -O-, -O-Ph-C(CH3)2-Ph-O-, -C(O)OR-OC(O)-, or -CH2-CH(-OC(O)CH3)-CH2-, Ph is a phenylene group, and R is a linear alkylene group having 1 to 20 carbon atoms.
[0017] Examples of aromatic tetracarboxylic acid anhydrides include pyromellitic dianhydride, 4,4'-oxydiphthalic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic acid dianhydride, 3,3',4,4'-diphenyl sulfone tetracarboxylic acid dianhydride, 1,2,3,4-benzene tetracarboxylic acid anhydride, 1,4,5,8-naphthalene tetracarboxylic acid anhydride, 2,3,6,7-naphthalene tetracarboxylic acid anhydride, 3,3',4,4'-biphenyl tetracarboxylic acid dianhydride, 2,2',3,3'-biphenyl tetracarboxylic acid dianhydride, 2,3,3',4'-biphenyl tetracarboxylic acid dianhydride, and 2,3,3',4'-biphenyl tetracarboxylic acid dianhydride. carboxylic acid dianhydride, 2,3,3',4'-benzophenone tetracarboxylic acid dianhydride, 2,3,3',4'-diphenyl ether tetracarboxylic acid dianhydride, 2,3,3',4'-diphenyl sulfone tetracarboxylic acid dianhydride, 2,2-bis(3,3',4,4'-tetracarboxyphenyl)tetrafluoropropane dianhydride, 2,2'-bis(3,4-dicarboxyphenoxyphenyl)sulfone dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, and 4,4'-[propane-2,2-diylbis(1,4-phenyleneoxy)]diphthalic dianhydride.
[0018] Examples of diamines having an ether bond include 4,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, bis[4-(3-aminophenoxy)phenyl]sulfoxide, bis[4-(4-aminophenoxy)phenyl]sulfoxide, (4-aminophenoxyphenyl)(3-aminophenoxyphenyl)phenyl]sulfoxide, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(aminophenoxy)phenyl]sulfone, (4-aminophenoxyphenyl) 4-(4-aminophenoxyphenyl)(3-aminophenoxyphenyl)phenyl]sulfone, bis[4-(3-aminophenoxyphenyl)phenyl]sulfide, bis[4-(aminophenoxy)phenyl]sulfide, (4-aminophenoxyphenyl)(3-aminophenoxyphenyl)phenyl]sulfide, bis[4-(3-aminophenoxy)phenyl]methane, bis[4-(4-aminophenoxy)phenyl]methane, [4-(4-aminophenoxyphenyl)][4-(3-aminophenoxyphenyl)]methane, 1,1-bis[4-(3-aminophenoxy)phenyl]ethane ethane, 1,1-bis[4-(4-aminophenoxy)phenyl]ethane, 1,1-[4-(4-aminophenoxyphenyl)][4-(3-aminophenoxyphenyl)]ethane, 1,2-bis[4-(3-aminophenoxy)phenyl]ethane, 1,2-bis[4-(4-aminophenoxy)phenyl]ethane, 1,2-[4-(4-aminophenoxyphenyl)][4-(3-aminophenoxyphenyl)]ethane, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane Pan, 2,2-[4-(4-aminophenoxyphenyl)][4-(3-aminophenoxyphenyl)]propane, 2,2-bis[3-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-[4-(4-aminophenoxyphenyl)][4-(3-aminophenoxyphenyl)]-1,1,1,3,3,3-hexafluoropropane, 1,3-bis(3-aminophenoxy)benzene, 1,4-bis(3-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, bis[4-(3-aminophenoxy)phenyl]ketone, bis[4-(4-aminophenoxy)phenyl]ketone, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-( 4-aminophenoxy)phenyl]ether, polytetramethylene oxide-di-p-aminobenzoate, poly(tetramethylene / 3-methyltetramethylene ether) glycol bis(4-aminobenzoate), 3,3'-diamino-4,4'-dicarboxydiphenyl ether, 4,4'-diamino-3,3'-dicarboxydiphenyl ether, 4,4'-diamino-2,2'-dicarboxydiphenyl ether and other diphenyl ethers; hydroxydiphenyl ethers such as 3,3'-diamino-4,4'-dihydroxydiphenyl ether, 4,4'-diamino-3,3'-dihydroxydiphenyl ether, and 4,4'-diamino-2,2'-dihydroxydiphenyl ether; Bis[(hydroxyphenyl)phenyl]alkane compounds such as 2,2-bis[4-(4-amino-3-hydroxyphenoxy)phenyl]propane; Bis(hydroxyphenoxy)biphenyl compounds such as 4,4'-bis(4-amino-3-hydroxyphenoxy)biphenyl; Bis[(hydroxyphenoxy)phenyl]sulfone compounds such as 2,2-bis[4-(4-amino-3-hydroxyphenoxy)phenyl]sulfone; Diamines containing propylene oxide chains such as poly(propylene glycol) diamine are also included. Examples of diamines having a siloxane bond include diamines containing a dimethylsiloxane group, such as 1,3-bis(3-aminopropyl)tetramethyldisiloxane.
[0019] Among these, from the viewpoints of adhesiveness and thermal conductivity, the diamine having an ether bond or a siloxane bond is preferably at least one selected from the group consisting of 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-diaminodiphenyl ether, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, poly(propylene glycol)diamine, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane.
[0020] That is, polyimide A is preferably a polyimide which is a reaction product of an aromatic tetracarboxylic acid anhydride and at least one diamine selected from the group consisting of 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-diaminodiphenyl ether, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, poly(propylene glycol)diamine, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane.
[0021] (Polyimide B) Polyimide B is a reaction product of an aromatic tetracarboxylic anhydride and a polyamine including an aliphatic diamine having 4 to 40 carbon atoms.
[0022] The preferred embodiments of the aromatic tetracarboxylic acid anhydride are as described above.
[0023] The carbon number of the aliphatic diamine having 4 to 40 carbon atoms is preferably 6 to 40, and more preferably 6 to 36. The aliphatic diamine having 4 to 40 carbon atoms may be used alone or in combination of two or more kinds.
[0024] The aliphatic diamine may be a saturated aliphatic diamine or an unsaturated fatty acid diamine.
[0025] The aliphatic diamine may be an aliphatic diamine containing a ring structure (alicyclic diamine) or an aliphatic diamine not containing a ring structure (non-cyclic aliphatic diamine).
[0026] The ring contained in the alicyclic diamine may be a monocyclic ring or a polycyclic ring. The ring contained in the alicyclic diamine may be one ring or two or more rings.
[0027] Examples of the ring contained in the alicyclic diamine include a cycloalkane ring such as a cyclohexane ring; a cycloalkene ring such as a cyclohexene ring; a bicycloalkane ring such as a norbornane ring; and a bicycloalkene ring such as norbornene. Among these, the ring contained in the alicyclic diamine is preferably a cycloalkane ring, more preferably a cycloalkane ring having 4 to 7 carbon atoms, and further preferably a cyclohexane ring.
[0028] The alicyclic diamine preferably has 6 to 22 carbon atoms, and more preferably has 8 to 17 carbon atoms.
[0029] Examples of alicyclic diamines include 1,2-bis(aminomethyl)cyclohexane, 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, 1,2-cyclohexanediamine, 1,3-cyclohexanediamine, 1,4-cyclohexanediamine, 4,4'-diaminodicyclohexylmethane, 4,4'-methylenebis(2-methylcyclohexylamine), carvonediamine, limonenediamine, isophoronediamine, norbornanediamine, bis(aminomethyl)tricyclo[5.2.1.02,6]decane, 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane, and 4,4'-diaminodicyclohexylpropane.
[0030] Acyclic aliphatic diamines are NH2-R 1 -NH2, R 1 is preferably an alkylene group. The number of carbon atoms in the alkylene group is preferably 5 to 16, more preferably 6 to 14, further preferably 7 to 12, and particularly preferably 8 to 10. The alkylene group may be linear or branched.
[0031] Examples of acyclic aliphatic diamines include 1,5-pentamethylenediamine, 2-methylpentane-1,5-diamine, 3-methylpentane-1,5-diamine, 1,6-hexamethylenediamine, 1,7-heptamethylenediamine, 1,8-octamethylenediamine, 1,9-nonamethylenediamine, 1,10-decamethylenediamine, 1,11-undecamethylenediamine, 1,12-dodecamethylenediamine, 1,13-tridecamethylenediamine, 1,14-tetradecamethylenediamine, and 1,16-hexadecamethylenediamine.
[0032] The aliphatic diamine having 4 to 40 carbon atoms may be a dimer diamine. A dimer diamine is a compound derived from a dimer acid, which is a dimer of an unsaturated fatty acid such as oleic acid (see JP-A-9-12712). An example of a dimer diamine is a compound represented by the following formula:
[0033] [ka]
[0034] [ka]
[0035] In the above formula, m+n=6-17, and p+q=8-19. Commercially available dimer diamine products include VERSAMINE (registered trademark) 551 (manufactured by BASF Japan), VERSAMINE (registered trademark) 552 (manufactured by BASF Japan, a hydrogenated product of VERSAMINE (registered trademark) 551), PRIAMINE 1075 (manufactured by Croda Japan), and PRIAMINE 1074 (manufactured by Croda Japan).
[0036] Polyimide B may be a reaction product of an aromatic tetracarboxylic anhydride, an aliphatic diamine having 4 to 40 carbon atoms, and a polyamine other than the aliphatic diamine having 4 to 40 carbon atoms. Examples of polyamines other than aliphatic diamines having 4 to 40 carbon atoms include aliphatic triamines having 6 to 40 carbon atoms.
[0037] The carbon number of the aliphatic triamine having 6 to 40 carbon atoms is preferably 10 to 30. The aliphatic triamine having 6 to 40 carbon atoms may be used alone or in combination of two or more kinds.
[0038] The aliphatic triamine may be a saturated aliphatic triamine or an unsaturated fatty acid triamine.
[0039] The aliphatic triamine may be an aliphatic diamine containing a ring structure (alicyclic triamine) or an aliphatic triamine not containing a ring structure.
[0040] The ring contained in the alicyclic triamine may be a monocyclic ring or a polycyclic ring. The ring contained in the alicyclic triamine may be one ring or two or more rings.
[0041] The aliphatic triamine having 6 to 40 carbon atoms may be a trimer triamine. Trimer triamine is a compound in which all carboxyl groups of trimer acid, which is a trimer of unsaturated fatty acid such as oleic acid (see JP2013-505345A, etc.), are substituted with primary amino groups. Examples of trimer triamine include compounds represented by the following formula:
[0042] [ka]
[0043] In the above formula, the dashed line represents a carbon-carbon single bond or a carbon-carbon double bond, and R represents an ethylene group (-CH2CH2-) or an ethenylene group (-CH=CH-).
[0044] Among these, from the viewpoints of adhesiveness and thermal conductivity, polyimide B is preferably a thermoplastic polyimide which is a reaction product of an aromatic tetracarboxylic acid anhydride, a non-cyclic aliphatic diamine having 4 to 40 carbon atoms, and an alicyclic diamine having 6 to 40 carbon atoms.
[0045] From the viewpoints of adhesion and thermal conductivity, polyimide B is preferably a thermoplastic polyimide which is a reaction product of an aromatic tetracarboxylic anhydride, an aliphatic diamine having 4 to 40 carbon atoms, and an aliphatic triamine having 6 to 40 carbon atoms.
[0046] The content of polyimide is 15 to 60% by volume, and preferably 15 to 40% by volume, based on the total volume of the power device sheet. The polyimide can be synthesized by a conventionally known method.
[0047] <Filler> The power device sheet of the present disclosure contains at least one type of filler selected from the group consisting of oxides, nitrides, elemental metals, alloys, and carbon.
[0048] Examples of oxides include zirconium oxide (ZrO2), titanium oxide (TiO2), silicon oxide (SiO2), aluminum oxide (Al2O3), iron oxide (Fe2O3, FeO, or Fe3O4), copper oxide (CuO or Cu2O), zinc oxide (ZnO), yttrium oxide (Y2O3), niobium oxide (Nb2O5), molybdenum oxide (MoO3), indium oxide (In2O3 or In2O), tin oxide ( Metal oxides such as SnO2), tantalum oxide (Ta2O5), tungsten oxide (WO3, or W2O5), lead oxide (PbO, PbO2), bismuth oxide (Bi2O3), cerium oxide (CeO2, or Ce2O3), antimony oxide (Sb2O3, or Sb2O5), germanium oxide (GeO2, or GeO), lanthanum oxide (La2O3), and ruthenium oxide (RuO2); and magnesium metasilicate.
[0049] Examples of nitrides include boron nitride (BN), carbon nitride (CN), silicon nitride (SiN), gallium nitride (GaN), indium nitride (InN), aluminum nitride (AlN), chromium nitride (CrN), copper nitride (CuN), iron nitride (FeN or FeN), lanthanum nitride (LaN), lithium nitride (LiN), magnesium nitride (MgN), molybdenum nitride (MoN), niobium nitride (NbN), tantalum nitride (TaN), titanium nitride (TiN), tungsten nitride (WN, WN2, or WN), yttrium nitride (YN), and zirconium nitride (ZrN).
[0050] Examples of elemental metals include gold, silver, copper, molybdenum, aluminum, titanium, chromium, zinc, nickel, platinum, palladium, and manganese.
[0051] The alloy may be, for example, an alloy made of two or more metal elements selected from the group consisting of gold, silver, copper, molybdenum, aluminum, titanium, chromium, zinc, nickel, platinum, palladium, and manganese.
[0052] Among these, from the viewpoints of adhesiveness and thermal conductivity, the filler is preferably at least one selected from the group consisting of metal oxides, boron nitride, and magnesium metasilicate, and more preferably boron nitride.
[0053] The shape of the filler is not particularly limited and may be any of granular, needle-like (fibrous) and plate-like. Specific shapes of the filler include spherical, scale-like, layered, leaf-like, apricot kernel-like, columnar, cockscomb-like, equiaxial, leaf-like, micaceous, block-like, flat, wedge-like, rosette-like, net-like and prismatic shapes.
[0054] From the viewpoint of adhesiveness, the average particle size of the filler is preferably from 0.01 to 20 μm, and more preferably from 0.1 to 10 μm. In the present disclosure, the average particle diameter of the filler means the volume average particle diameter (D50), which is the cumulative 50% diameter of the particles based on the volume determined by the laser diffraction / scattering method. That is, the particle size distribution is measured by the laser diffraction / scattering method, a cumulative curve is obtained with the total volume of the particle group being 100%, and the particle diameter is the point on the cumulative curve where the cumulative volume is 50%. The D50 of the filler is determined by dispersing the particles in water and analyzing them by the laser diffraction / scattering method using a laser diffraction / scattering type particle size distribution measuring device (for example, the laser diffraction / scattering particle size distribution measuring device "LS-13 320" manufactured by Beckman Coulter, Inc.).
[0055] The content of the filler is 40 to 85% by volume, and preferably 60 to 85% by volume, based on the total amount of the power device sheet.
[0056] <Other ingredients> The sheet for power devices of the present disclosure may contain components other than the polyimide and the filler. Examples of other components include dehydrating agents, plasticizers, weathering agents, antioxidants, heat stabilizers, lubricants, antistatic agents, brightening agents, colorants, conductive agents, release agents, surface treatment agents, viscosity adjusters, and flame retardants.
[0057] <Method of manufacturing power device sheets> The power device sheet containing a polyimide and a filler can be produced, for example, by applying a composition containing a polyimide and a filler onto a support and then drying the composition.
[0058] <Thermal conductivity> The power device sheet of the present disclosure has a thermal conductivity of 5 W / (m K) or more, preferably 7 W / (m K) or more, and more preferably 10 W / (m K) or more. The upper limit of the thermal conductivity is, for example, 100 W / (m K). The thermal conductivity can be measured using a thermal conductivity measuring device (UNITEM MODEL2022, manufactured by Anter Corporation).
[0059] <Thickness> The power device sheet of the present disclosure has a thickness of 200 μm or less, preferably 150 μm or less, and more preferably 100 μm or less. The thickness was determined by measuring the thickness at eight points using a thickness meter (model: H-type 2.4N, manufactured by PEACOCK Company) at the four corners of the measurement sample and at four points 1 cm away from the edges at the center of the four sides, and then calculating the average thickness.
[0060] Although the sheet for power devices according to the present disclosure has a thickness of 200 μm or less, it has excellent adhesiveness and thermal conductivity because it contains polyimide A or polyimide B. Therefore, it is suitable for use in power devices. In particular, the power device sheet of the present disclosure is suitable as a silicon carbide-based power device sheet.
[0061] The sheet for power devices of the present disclosure is also preferably used for bonding a power module, such as a silicon carbide-based power module, to a cooler. A power module is a package in which a plurality of power elements (power MOSFETs, IGBTs, etc.) are connected to a ceramic substrate or the like. The power module may be configured such that the power elements are provided on the front side and heat is released from the back side, or may be configured such that heat can be released from both sides. The cooler is preferably one that can cool the power module by heat exchange, and may be water-cooled or air-cooled. A cooler can be directly bonded to both sides of a power module configured to dissipate heat from both sides, via the sheet for power device of the present disclosure.
[0062] [Power device components] A power device member according to the present disclosure is a power device member in which a polyimide sheet and a metal sheet are laminated, the polyimide sheet containing polyimide and at least one filler selected from the group consisting of oxides, nitrides, elemental metals, alloys, and carbides, the polyimide content being 40 to 80% by volume with respect to the total amount of the polyimide sheet, and the filler content being 20 to 60% by volume with respect to the total amount of the polyimide sheet, the polyimide being polyimide A which is a reaction product of an aromatic tetracarboxylic anhydride and a diamine having an ether bond or a siloxane bond, or polyimide B which is a reaction product of an aromatic tetracarboxylic anhydride and a polyamine including an aliphatic diamine having 4 to 40 carbon atoms, and the sheet having a thermal conductivity of 5 W / (m·K) or more and a thickness of 200 μm or less.
[0063] The preferred aspects of the polyimide sheet are the same as those of the above-mentioned power device sheet.
[0064] Examples of metals contained in the metal sheet include Cu (copper), Au (gold), Ag (silver), and Al (aluminum). The thickness of the metal sheet is not particularly limited and is, for example, 5 μm to 300 μm.
[0065] The power device component of the present disclosure is a power device component in which a polyimide sheet and a metal sheet are laminated, and although it is thin, having a thickness of 200 μm or less, it has excellent adhesion and thermal conductivity because it contains polyimide A or polyimide B as the polyimide. In particular, the power device components of the present disclosure are suitable for silicon carbide-based power device components. EXAMPLES
[0066] The present invention will be described in more detail below using examples, but the present invention is not limited to these examples.
[0067] <Example 1> Referring to the examples in JP 2023-047876 A, a polyamic acid solution was obtained using 3,3',4,4'-biphenyltetracarboxylic dianhydride and 4,4'-oxydiphthalic acid as tetracarboxylic anhydrides and paraphenylenediamine and 1,3-bis(4-aminophenoxy)benzene as polyamines, and boron nitride filler (average particle size: 7 μm) was added to the solution. The solution was then cast onto aluminum foil and dried to obtain a gel sheet. The gel sheet was then heated in a hot air circulating oven to cause a ring-closing reaction of the polyamic acid, and a sheet (thickness: 100 μm, thermal conductivity: 8 W / (m·K)) containing 35% by volume of polyimide and 65% by volume of boron nitride filler was obtained.
[0068] <Example 2> Referring to the examples in JP 2017-186551 A, a polyimide solution was obtained using 4,4'-[propane-2,2-diylbis(1,4-phenyleneoxy)]diphthalic dianhydride as the tetracarboxylic anhydride and a mixture of dimer diamine and trimer triamine as the polyamine, and then boron nitride filler (average particle size: 7 μm) was added to the obtained polyimide solution. The solution was then cast onto a polytetrafluoroethylene sheet and dried to obtain a sheet (thickness: 100 μm, thermal conductivity: 10 W / (m·K)) containing 45% by volume of polyimide and 55% by volume of boron nitride filler.
[0069] <Example 3> Referring to the examples in Japanese Patent No. 7040692, a powder of polyimide obtained using pyromellitic dianhydride as the tetracarboxylic anhydride and 1,3-bis(aminomethyl)cyclohexane and 1,8-octamethylenediamine as the polyamine was dry-blended with boron nitride filler (average particle size: 7 μm), and melt-extruded in a co-rotating twin-screw kneading extruder to obtain pellets. The obtained pellets were melt-molded to obtain a sheet (thickness: 100 μm, thermal conductivity: 7 W / (m·K)) containing 65% by volume of polyimide and 35% by volume of boron nitride filler.
[0070] <Sheet evaluation> The electrical insulation of each of the sheets obtained in Examples 1 to 3 was measured using a dielectric breakdown tester under conditions of 30 kV and 10 mA, and the electrical insulation of the sheets was found to be 5 Kv or more. Each sheet was sandwiched between two aluminum plates and heat-pressed (180°C, 1 MPa, 60 minutes) to obtain a press laminate. The adhesive strength of this press laminate was measured using a Tensilon tester in accordance with JIS K 6850-1999, and was found to be 10 MPa or more for all laminates using the sheets.
[0071] It was found that the sheets of Examples 1 to 3 were excellent in adhesiveness and thermal conductivity and were useful as sheets for power devices.
Claims
1. Polyimide and and at least one filler selected from the group consisting of oxides, nitrides, simple metals, alloys, and carbon, the content of the polyimide is 15 to 60% by volume with respect to the total amount of the power device sheet, The content of the filler is 40 to 85% by volume with respect to the total amount of the power device sheet, The polyimide includes polyimide A which is a reaction product of an aromatic tetracarboxylic anhydride and a diamine having an ether bond or a siloxane bond, or polyimide B which is a reaction product of an aromatic tetracarboxylic anhydride and a polyamine including an aliphatic diamine having 4 to 40 carbon atoms; A sheet for power devices having a thermal conductivity of 5 W / (m·K) or more and a thickness of 200 μm or less.
2. The polyimide A is a polyimide that is a reaction product of an aromatic tetracarboxylic acid anhydride and at least one diamine selected from the group consisting of 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-diaminodiphenyl ether, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, poly(propylene glycol)diamine, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane. The power device sheet according to claim 1.
3. The polyimide B is a thermoplastic polyimide that is a reaction product of an aromatic tetracarboxylic acid anhydride, an aliphatic diamine having 4 to 40 carbon atoms and not having a ring structure, and an aliphatic diamine having 6 to 40 carbon atoms and including a ring structure. The power device sheet according to claim 1.
4. The polyimide B is a thermoplastic polyimide that is a reaction product of an aromatic tetracarboxylic anhydride, an aliphatic diamine having 4 to 40 carbon atoms, and an aliphatic triamine having 6 to 40 carbon atoms. The power device sheet according to claim 1.
5. 2. The power device sheet according to claim 1, wherein the filler is at least one selected from the group consisting of metal oxides, boron nitride, and magnesium metasilicate.
6. 2. The sheet for power devices according to claim 1, which is a sheet for silicon carbide-based power devices.
7. A power device member in which a polyimide sheet and a metal sheet are laminated, The polyimide sheet is Polyimide and At least one filler selected from the group consisting of oxides, nitrides, metal elements, alloys, and carbon; The content of the polyimide is 15 to 60% by volume based on the total amount of the polyimide sheet, the content of the filler is 40 to 85% by volume based on the total amount of the polyimide sheet; The polyimide includes polyimide A which is a reaction product of an aromatic tetracarboxylic anhydride and a diamine having an ether bond or a siloxane bond, or polyimide B which is a reaction product of an aromatic tetracarboxylic anhydride and a polyamine including an aliphatic diamine having 4 to 40 carbon atoms; A power device member which is a sheet having a thermal conductivity of 5 W / (m·K) or more and a thickness of 200 μm or less.
8. The power device component according to claim 7 , wherein the power device component is a silicon carbide based power device component.
Citation Information
Patent Citations
Polyimide resin composition and thermal conductive adhesive film using the same
JP2015108139A